2004
DOI: 10.1093/petrology/egg103
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Evolution of Silica-saturated Alkalic Suites: an Experimental Study

Abstract: Experimental simulation of incremental crystal fractionation of a hy-normative hawaiite indicates that the spectrum of compositions from mildly alkalic hawaiite to sodic rhyolite found in silica-saturated alkalic suites of the ocean islands and continental hotspots and rifts can be produced by fractionation at 9Á3 kbar with bulk water contents 4$0Á5 wt % (in the hawaiite) at f O 2 $1Á5 log units below the fayalite-magnetite-quartz buffer (FMQ). Along this path, mildly alkalic basalt becomes increasingly alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 43 publications
(80 reference statements)
12
118
1
5
Order By: Relevance
“…Experimental studies of hydrous mafic magmas crystallization indicate that usually olivine and clinopyroxene are the liquidus phases and amphibole saturates after these mineral phases (e.g., Nekvasil et al, 2004;Krawczynski et al, 2012. ) in accordance with our textural observations of the poikilitic samples.…”
Section: Evolution Of Cumulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of hydrous mafic magmas crystallization indicate that usually olivine and clinopyroxene are the liquidus phases and amphibole saturates after these mineral phases (e.g., Nekvasil et al, 2004;Krawczynski et al, 2012. ) in accordance with our textural observations of the poikilitic samples.…”
Section: Evolution Of Cumulatesmentioning
confidence: 99%
“…Both temperature and melt composition can potentially affect our empirical barometer increasing the uncertainty of the pressure estimation. Therefore we analysed the effect of temperature and melt composition using the extensive experimental dataset of Nekvasil et al (2004). Fig.…”
Section: Crystallization Conditionsmentioning
confidence: 99%
“…In this paper the authors investigated the amphibole composition within rocks with a well-defined chemical/mineralogical composition (under well-defined conditions: temperature, pressure and H2O-content). Nekvasil et al (2004) reported that the rock types and amphibole compositions are similar to the DAM rock types and amphibole compositions, so it is an appropriate reference for the estimation of the pressure and temperature of alkaline systems. The best results were given for the ultramafic cumulate rocks' amphiboles by the oxo-hygro-thermobarometer provided by Ridolfi and Renzulli (2012) which was calibrated for alkaline systems.…”
Section: Introductionmentioning
confidence: 82%
“…A termobarométerek eredményeit összehasonlítottuk egymással és kísérleti adatokkal is. A kísérleti adatoknál Nekvasil et al (2004) munkáját vettük alapul, amelyben ismert összetételű kőzetekben, meghatározott kristályosodási körülmények között vizsgálták a keletkezett amfibolok összetételét. A Nekvasil et al (2004) munkájában használt kőzettípusok és azok amfibol adatai nagy hasonlóságot mutatnak a DAM kőzeteivel és amfibol összetételeivel, így megfelelő referenciaforrás egy alkáli rendszer nyomás és hőmérséklet becslésének megállapítására.…”
Section: Petrogenezisunclassified
See 1 more Smart Citation